2017
DOI: 10.1292/jvms.16-0576
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary oregano essential oil and vitamin E supplementation on meat quality, stress response and intestinal morphology in pigs following transport stress

Abstract: This study investigates the effects of dietary oregano essential oil (OEO) and vitamin E (Vit E) supplementation on meat quality, stress response and intestinal morphology in pigs following transport stress. A total of 288 finishing pigs were randomly assigned to three groups: a basal diet or a basal diet supplemented either with 200 mg/kg Vit E or 25 mg/kg OEO. After a 28-day feeding trial, total of 132 finishing pigs according diet and transport stress were assigned to one of four treatment groups: 1) contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 34 publications
(37 reference statements)
1
28
0
2
Order By: Relevance
“…Besides preventing agonistic interactions from happening, an optimal ratio of fat, cholesterol and carbohydrate can even promote positive non-agonistic social interactions (52). Stress levels and fearful emotions can also be decreased with a large range of feed supplementation: vitamin E (46,53), magnesium (47), tryptophan (48,(54)(55)(56), aromatic plant extracts (53,57), chitosan (58), and the ratios of fat, cholesterol, carbohydrate (52), and linoleic acid in the diet (59). Finally, tryptophan has also demonstrated consistent effects in terms of reduction of aberrant behaviors, such as tail biting (49,60), as well as changes in exploration in behavioral tests (61,62).…”
Section: Discussionmentioning
confidence: 99%
“…Besides preventing agonistic interactions from happening, an optimal ratio of fat, cholesterol and carbohydrate can even promote positive non-agonistic social interactions (52). Stress levels and fearful emotions can also be decreased with a large range of feed supplementation: vitamin E (46,53), magnesium (47), tryptophan (48,(54)(55)(56), aromatic plant extracts (53,57), chitosan (58), and the ratios of fat, cholesterol, carbohydrate (52), and linoleic acid in the diet (59). Finally, tryptophan has also demonstrated consistent effects in terms of reduction of aberrant behaviors, such as tail biting (49,60), as well as changes in exploration in behavioral tests (61,62).…”
Section: Discussionmentioning
confidence: 99%
“…Transportation is a crucial factor influencing intestine structure and function, meat quality and slaughter efficiency in pigs (Zou et al, 2017). It has been demonstrated that transport stress may induce intestinal oxidative stress, which contributes to intestinal dysfunction (Wei, Xue, Zhou, & Peng, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Each group had eight pigs. Pigs were transported using the method previously described (Zou et al, ). The control group were directly transported to the abattoir (2‐hr journey) a day prior to slaughter and housed in resting pens for 24 hr (14:00 to next day 14:00) with water ad libitum before slaughter.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations